STATUS OF AMERICAN COOT FULICA AMERICANA (GRUIFORMES: RALLIDAE) WINTERING IN MEXICO - Pérez-Arteaga, Alejandro; Gaston, Kevin J. (Instituto de Ecología, A.C., 2022)
We determined population trends and important sites for American coot (Fulica americana) wintering in Mexico, for which population information in the country is practically inexistent. The long-term (1960-2000) distribution of the population wintering in the country was: Gulf of Mexico coast (68%), upper Pacific coast (20%), central highlands (7%), northern highlands (3%), lower Pacific coast (2%). The short-term (1991-2000) distribution was 53%, 30%, 8%, 5% and 3%, respectively. Numbers decreased from 1981 until 1997, but no significant long-term or short-term linear trends were detected in the overall national population. The national short-term average of around 210,000 American coot was 52% below (P < 0.05) the long-term average of around 450,000. In the Gulf of Mexico coast, a significant decline was detected (-2.4% per year, P < 0.05). Other regions showed no significant trends. American coots are widespread throughout the country, but large concentrations occur only on a few locations. During 1991-2000, American coot were recorded in 76% of the count sites, but six sites alone held 71% of the national total (Tamesi and Pánuco river deltas 17.8%, Ensenada Pabellón 15.6%, Topolobampo 9.1%, Campeche-Yucatán lagoons 17.8%, Tabasco lagoons 6.7%, Laguna Madre 3.8%). The former three sites qualify as wetlands of international importance under the Ramsar Convention, by having on average more than 20,000 American coot. The cause for decreasing numbers, especially in the Gulf Coast, the extent of resident populations, and the role of the species as an indicator of wetland health should be subject to further investigation.